2019
DOI: 10.3177/jnsv.65.343
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Athletes Choose Dietary Supplements? Reliability and Validity of the Dietary Supplement Choice Questionnaire (DSCQ) among Japanese College Athletes

Abstract: To assess the reliability and validity of the Dietary Supplement Choice Questionnaire (DSCQ) to capture dietary supplement choice motives among Japanese college athletes. The cross-sectional study was performed in 2014. This study recruited 1,451 college athletes from sports-oriented clubs at the University of Tsukuba, Japan. The participants completed the DSCQ, health literacy, and subjective economic status; part of the participants completed a test-retest (n5378). A sample of 975 participants (28.0% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was observed that the majority of the athletes did not prefer to use ergogenic support, and the rate of those who preferred was 24.6%. It is known that 'popularity, functionality, price, taste, convenience, antidoping and familiarity' are among the reasons for adolescent athletes prefer ergogenic supplements (Kakutani et al, 2019). In a study conducted in Türkiye, including adolescent martial athletes, it was determined that 22.6% of the athletes used ergogenic support, and they used ergogenic supports to 'improve performance, lose weight, increase muscle mass, increase energy level, health and satiety' (Çamaşırcı, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the majority of the athletes did not prefer to use ergogenic support, and the rate of those who preferred was 24.6%. It is known that 'popularity, functionality, price, taste, convenience, antidoping and familiarity' are among the reasons for adolescent athletes prefer ergogenic supplements (Kakutani et al, 2019). In a study conducted in Türkiye, including adolescent martial athletes, it was determined that 22.6% of the athletes used ergogenic support, and they used ergogenic supports to 'improve performance, lose weight, increase muscle mass, increase energy level, health and satiety' (Çamaşırcı, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An examiner explained the general purpose and outline of the survey to participants who were college athletes belonging to the club of the university. Details of the study design and participant characteristics have been reported elsewhere (13).…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study was performed with a selfwritten questionnaire for college athletes who belonged to the sports club of the University of Tsukuba (Ibaraki, Japan) from October to December 2014. Details of the study design and participant characteristics have been reported elsewhere (10).…”
Section: Participants and Study Designmentioning
confidence: 99%